If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (z + 1) = 2(3 + -2z) + 17 Reorder the terms: (1 + z) = 2(3 + -2z) + 17 Remove parenthesis around (1 + z) 1 + z = 2(3 + -2z) + 17 1 + z = (3 * 2 + -2z * 2) + 17 1 + z = (6 + -4z) + 17 Reorder the terms: 1 + z = 6 + 17 + -4z Combine like terms: 6 + 17 = 23 1 + z = 23 + -4z Solving 1 + z = 23 + -4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '4z' to each side of the equation. 1 + z + 4z = 23 + -4z + 4z Combine like terms: z + 4z = 5z 1 + 5z = 23 + -4z + 4z Combine like terms: -4z + 4z = 0 1 + 5z = 23 + 0 1 + 5z = 23 Add '-1' to each side of the equation. 1 + -1 + 5z = 23 + -1 Combine like terms: 1 + -1 = 0 0 + 5z = 23 + -1 5z = 23 + -1 Combine like terms: 23 + -1 = 22 5z = 22 Divide each side by '5'. z = 4.4 Simplifying z = 4.4
| 16x+10+5x+2=180 | | 32=3x+9 | | (4x-20)= | | y-x=32 | | ((9x-11)+(7x-3))=((4x+1)(4x+1)) | | -9x-3x+4=-10x-(2x-4) | | 288=27x+18 | | 5(2h+3)-4h= | | 90=-5x-5(x-8) | | -8x+9=2x+49 | | 2x-5-4x=17 | | 11+20x=22x-1 | | 20/258 | | -x+4q=41 | | A=77-14.99n | | 9b+4=-23 | | 0=9-1/50x^2 | | -201=4n+7(1-8n) | | -3x-5(x-2)=4 | | 8r^4-r^2= | | 2h+(6h+h)+12= | | 4x+10h=5x+17 | | x^4+3x^3-3x^2-7x+6=0 | | -2+13x=50 | | 3x^3-15x^2-12x=0 | | x+6y=164 | | 3x-17=50 | | 3x+(x)+2=x+5 | | Log27(5x-1)=1/3 | | 23.24=4g+3.84 | | 3x+7=11+4x | | 2x-3(x+4)=21 |